Papers relative to the recent Arctic expeditions in search of Sir John Franklin and the crews of H.M.S. "Erebus" and "Terror" [electronic resource]. - Great Britain. Admiralty. (London : G.E. Eyre and W. Spottiswoode, 1854)
Original issued in series: [Command papers / Great Britain. Parliament C. 1725] Attributed to Great Britain. Admiralty--National Union Catalog pre-1956 imprints. "Presented to both Houses of Parliament by command of Her Majesty." Electronic reproduction. Mode of access: Internet. 44